ANALISIS OPTIMALISASI KINERJA KARYAWAN MELALUI DIGITALISASI BISNIS DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN UMUM PERCETAKAN UANG REPUBLIK INDONESIA (PERUM PERURI) DIREKTORAT SDM DAN UMUM - Edi Suswardji; Syaefudin Aziz; Rysmi Wulandari (POLITEKNIK PIKSI GANESHA, 2020)
The object of this research is the employees of Perum Peruri, Directorate HR and General. The research’s method is descriptive verification, with data sources utilized are primary and secondary. From the population of 256 people, the sample was taken using a Probability sampling especially Proportionate Stratified Random Sampling obtained as many as 156 people. To measure the level of employees performance toward business digitalization with organizational culture as an intervening variable, processing data using path analysis with the SPSS 16 software application. The results showed that the implementation of business digitalization is assessed good by employees, organization culture is assessed good by employees and in general, optimization of employee performance is assessed good by employees. It is proved that business digitalization influence organizational culture and the level of influence is strong. It is proved that business digitalization influence employees performance and the level of influence is strong enough. It is proved that organization culture influence employees performance and the level of influence is strong. Keywords : Business Digitalization, Organization Culture, Employees Performance.